2005
DOI: 10.1016/j.icesjms.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal variability in the Gulf of Maine zooplankton community, with potential impacts on fish recruitment

Abstract: We used principal component analysis (PCA) to explore interannual changes in a time-series lasting more than 40 years of zooplankton abundance from NOAA's Continuous Plankton Recorder (CPR) survey. This analysis identified a complex of taxa, including Centropages typicus, Oithona spp., Pseudocalanus spp., and Metridia lucens that followed a common pattern of interdecadal variability characterized by a dramatic increase in these taxa around 1990, followed by a rapid decline in 2002. All of these taxa showed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 34 publications
(41 reference statements)
11
119
0
1
Order By: Relevance
“…The medium-sized luminescent copepod M. lucens was significantly correlated to biomass trends throughout the northern half of the ecosystem. Its maximum abundance is measured in the Gulf of Maine, where increased primary productivity in winter has produced high abundance levels (Pershing et al, 2005). Though under-sampled in our nets, the interannual variability of the cyclopoid copepod Oithona spp.…”
Section: Discussionmentioning
confidence: 97%
“…The medium-sized luminescent copepod M. lucens was significantly correlated to biomass trends throughout the northern half of the ecosystem. Its maximum abundance is measured in the Gulf of Maine, where increased primary productivity in winter has produced high abundance levels (Pershing et al, 2005). Though under-sampled in our nets, the interannual variability of the cyclopoid copepod Oithona spp.…”
Section: Discussionmentioning
confidence: 97%
“…The increased stratification and associated phytoplankton production coincided with a reorganization of the zooplankton assemblage, with populations of smaller, shelf-associated copepods, like Centropages typicus, Metridia lucens, Oithona spp., and Pseudocalanus spp., increasing significantly in abundance (Fig. 4c) (Durbin et al 2003, Pershing et al 2005. Early copepodid stages of Calanus finmarchicus also increased in abundance with these smaller species; however, later copepodid stages of this more oceanic species declined in abundance (Fig.…”
Section: Regime Shift In the Northwest Atlanticmentioning
confidence: 87%
“…4d). Pershing et al (2005) have suggested that increased size-selective predation by herring may have been behind these paradoxical observations for C. finmarchicus. The largest increases in small copepod abundance were observed during late autumn/early winter, a change associated with the enhanced autumn phytoplankton blooms (Durbin et al 2003).…”
Section: Regime Shift In the Northwest Atlanticmentioning
confidence: 99%
“…The autumn phytoplankton color index is the mean autumn color index anomaly calculated from gulf of Maine continuous plankton recorder (goM cpr) survey data (greene and pershing, 2007). The Small copepod abundance index is the first mode from a pca of annual small copepod abundance anomalies calculated from goM cpr survey data (Technical note 6;pershing et al, 2005). The C. finmarchicus abundance index is the mean abundance anomaly calculated each year from goM cpr survey data; it is calculated separately for early juveniles (copepodites 1-4) and late stages (copepodite 5 and adults) of this species (pershing et al, 2005).…”
Section: E R I C a H E A D P E T E R S M I T H A N D A L E S S A mentioning
confidence: 99%
“…The C. finmarchicus abundance index is the mean abundance anomaly calculated each year from goM cpr survey data; it is calculated separately for early juveniles (copepodites 1-4) and late stages (copepodite 5 and adults) of this species (pershing et al, 2005). Size-selective predation by herring on the larger and older stages of C. finmarchicus may explain this apparent paradox (Pershing et al, 2005).…”
Section: E R I C a H E A D P E T E R S M I T H A N D A L E S S A mentioning
confidence: 99%